Dualisme Keadilan Retributif dan Restoratif dalam Sistem Peradilan Pidana Indonesia - Agustin, Ayu; Sulchan, Achmad (Jurnal Sosial Teknologi, 2025)
Indonesia's criminal justice system shows a dynamic between two paradigms of justice, namely retributive justice and restorative justice. Retributive justice is oriented towards punishing perpetrators with the aim of providing a deterrent effect, while restorative justice focuses on restoring the relationship between perpetrators, victims, and society. This study uses normative juridical methods with legislative, conceptual, and case approaches, to analyze the implementation and challenges of dualism of the two paradigms. The results of the study show that the Indonesian criminal justice system is still dominated by the retributive paradigm, as reflected in the Criminal Code and criminal practices. However, regulatory developments such as Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, Police Regulation Number 8 of 2021, and the new Criminal Code of 2023 show the strengthening of the restorative paradigm. The main challenges faced are regulatory consistency, resistance of law enforcement officials, and public acceptance. In conclusion, although the retributive paradigm is still strong, Indonesia's criminal justice system is beginning to move towards balance by making room for a restorative approach.